Neuromapping olfactory stimulation using magnetoencephalography - visualizing smell, a proof-of-concept study - Tarfa, Rahilla; Yu, Sophie E.; Ahmed, Omar H.; Moore, John A.; Bruña, Ricardo; Velasquez, Nathalia; Poplawsky, Alexander J.; Coffman, Brian A.; Lee, Stella E. (Frontiers in Allergy, 2023)
Importance Currently, clinical assessment of olfaction is largely reliant on subjective methods that require patient participation. The objective method for measuring olfaction, using electroencephalogram (EEG) readings, can be supplemented with the improved temporal resolution of magnetoencephalography (MEG) for olfactory measurement that can delineate cortical and peripheral olfactory loss. MEG provides high temporal and spatial resolution which can enhance our understanding of central olfactory processing compared to using EEG alone. Objective To determine the feasibility of building an in-house portable olfactory stimulator paired with electrophysiological neuroimaging technique with MEG to assess olfaction in the clinical setting. Design, setting and participants This proof-of-concept study utilized a paired MEG-olfactometer paradigm to assess olfaction in three normosmic participants. We used a two-channel olfactory stimulator to deliver odorants according to a programmed stimulus-rest paradigm. Two synthetic odorants: 2% phenethyl alcohol (rose) and 0.5% amyl acetate (banana) were delivered in increasing increments of time followed by periods of rest. Cortical activity was measured via a 306-channel MEG system. Main outcomes and measures Primary outcome measure was the relative spectral power for each frequency band, which was contrasted between rest and olfactory stimulation. Results Compared to rest, olfactory stimulation produced a 40% increase in relative alpha power within the olfactory cortex bilaterally with both odorants. A 25%–30% increase in relative alpha power occurred in the left orbitofrontal cortex and precentral gyrus with phenethyl alcohol stimulation but not amyl acetate. Conclusion and relevance In this proof-of-concept study, we demonstrate the feasibility of olfactory measurement via an olfactometer-MEG paradigm. We found that odorant-specific cortical signatures can be identified using this paradigm, setting the basis for further investigation of this system as a prognostic tool for olfactory loss.